2018
DOI: 10.31973/aj.v2i126.45
|View full text |Cite
|
Sign up to set email alerts
|

Post-Divorce Experiences in Jordan: A Phenomenological Perspective

Abstract: This study analyzes the post-divorce experiences of a sample of 50 Jordanian divorced participants. Qualitative and exploratory results are similar to the results of other studies that were conducted in certain western cultures. Similar issues included modern reasons for exiting a marriage, men's experiences of losing children and women's poor financial circumstances. Despite changes in the structure and function of the Jordanian family, post-divorce experiences continue to be influenced by the major factors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“….’. Hence, this result is consistent with the fact that Emirati spouses have an emotional divorce (showing no concern for their spouse’s feelings) that reflects the low quality of the practices of intimacy (Al Hourani and Al Garbawi, 2020).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“….’. Hence, this result is consistent with the fact that Emirati spouses have an emotional divorce (showing no concern for their spouse’s feelings) that reflects the low quality of the practices of intimacy (Al Hourani and Al Garbawi, 2020).…”
Section: Resultssupporting
confidence: 84%
“…Research on marital satisfaction in the UAE has shown that Emirati men were more satisfied with their marriages than women because of gender discrimination; they are heads of their families and have more independence and social support, and their experience is less distressing (Al-Darmaki et al, 2016; Al-Othman, 2012). In addition, research has shown that young Emirati women experiencing violence, a dearth of emotional bonds and effective communication in spousal relationships, and the control that their husbands exerted over them, contributed to marital dissatisfaction (Al Hourani and Al Garbawi, 2020; Bromfield, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation